2015
DOI: 10.12657/denbio.074.003
|View full text |Cite
|
Sign up to set email alerts
|

Storage compounds, ABA and fumarase in Fagus sylvatica embryos during stratification

Abstract: Understanding the mechanisms of seed dormancy is essential for planning optimal seed storage and for breaking the dormancy of stored seeds. Our experiments focused on three aspects of characterization of breaking the dormancy of Fagus sylvatica seeds during moist low temperature stratification. 1) We used the changes of ABA content in embryos during the whole process of stratification as the marker of the depth of dormancy: the decrease in the depth of dormancy (according standard germination tests) was direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Phenol compounds often are strongly inhibitory toward seed germination (Han et al, 2001;Samajdar et al, 2018;Zhao et al, 2018). In addition, ABA is an important plant hormone involved in many biological processes, including the regulation of seed dormancy and germination (Bian et al, 2018;Eli a sov a et al, 2015;Samajdar et al, 2018). On the basis of the changes to their relative contents, 1,2,3-benzenetriol and ABA were identified as putative endogenous inhibitors of C. chinensis seed germination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenol compounds often are strongly inhibitory toward seed germination (Han et al, 2001;Samajdar et al, 2018;Zhao et al, 2018). In addition, ABA is an important plant hormone involved in many biological processes, including the regulation of seed dormancy and germination (Bian et al, 2018;Eli a sov a et al, 2015;Samajdar et al, 2018). On the basis of the changes to their relative contents, 1,2,3-benzenetriol and ABA were identified as putative endogenous inhibitors of C. chinensis seed germination.…”
Section: Resultsmentioning
confidence: 99%
“…ABA is one of the major plant hormones involved in many biological processes, especially in the regulation of seed dormancy and germination (Bian et al, 2018;Eli a sov a et al, 2015;Samajdar et al, 2018). Earlier studies concluded that ABA sensitivity is correlated with the extent of the dormancy of mature seeds (Bewley and Black, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Beech seed germination manifested by embryonic axis elongation begins at approximately the 12th week of cold stratification [ 5 ]. Importantly, in beech seeds subjected to germination, protein storage vacuoles have been reported to diminish or disappear after the first week of stratification and were mostly utilized at the final stage of stratification [ 49 ]. In this context, MsrB1 and MsrB2 are suggested to be involved in proper storage material utilization in beech seeds prior to germination.…”
Section: Discussionmentioning
confidence: 99%
“…Beech seeds accumulate lipids, mainly triacylglycerols [53,54] and proteins [54,55]. Cotyledons contained twice as many total proteins and lipids as elongating embryonic axes when germination third phase was initiated.…”
Section: Discussionmentioning
confidence: 99%